Unilateral and Bilateral Audiological Benefit With an Adhesively Attached, Noninvasive Bone Conduction Hearing System. Issue 8 (September 2018) - Gawliczek, Tom; Munzinger, Fabio; Anschuetz, Lukas; Caversaccio, Marco; Kompis, Martin; Wimmer, Wilhelm
Abstract : Objective: To assess the audiological benefit of a noninvasive, adhesively attached bone conduction device (BCD1) in subjects with induced bilateral conductive hearing loss. Secondary objectives were to evaluate the additional benefit of bilateral fitting compared with unilateral fitting and to compare the outcomes with bone conduction devices attached to a softband (BCD2). Study Design: Prospective nonrandomized crossover study. Setting: Tertiary referral center. Patients: Fifteen subjects with induced bilateral conductive hearing loss. Main Outcome Measures: Sound field thresholds, speech understanding in quiet and in multinoise were assessed in unaided, unilateral, and bilateral treatment conditions. In addition, sound localization was evaluated in uni- and bilateral treatment conditions. Results: The outcomes of BCD1 and BCD2 were comparable. Sound field thresholds improved by 24.6 dB (BCD1) and 24.8 dB (BCD2) in the unilateral and 26.8 dB (BCD1) and 25.1 dB (BCD2) in the bilateral treatment condition. Speech reception thresholds (SRTs) in quiet improved by 20.0 dB (BCD1) and 21.7 dB (BCD2) in the unilateral and by 22.7 dB (BCD1) and 21.5 dB (BCD2) in the bilateral condition. If speech was presented from the front, SRTs in noise were improved by 3.6 dB and 4.2 dB (unilateral) and by 4.5 dB and 4.4 dB (bilateral) for BCD1 and BCD2, respectively. With speech presented from the unilateral side, SRTs were improved by 4.0 dB and 4.7 dB (unilateral) and 3.8 dB and 4.8 dB (bilateral) compared with the unaided situation. If noise was presented from the contralateral side, small differences (−0.6 dB and −0.1 dB) were observed. Bilateral fitting brought additional benefits for speech understanding in noise and sound localization. Conclusions: Both bone conduction devices seem to be a valid treatment for patients with conductive hearing loss and minor sensorineural hearing loss component. Abstract : Supplemental Digital Content is available in the text